A method for bidirectional active vibration control of structure using discrete-time sliding mode. Issue 13 (2018) - Paul, Satyam; Yu, Wen; Jafari, Raheleh
Abstract: In this paper, a novel discrete-time sliding mode control is proposed in order to attenuate structural vibration due to earthquake forces. The analysis is based on the lateral-torsional vibration under the bidirectional waves. The proposed fuzzy modeling based sliding mode control can reduce chattering due to its time-varying gain. In the modeling equation of the structural system, the uncertainty exists in terms of sti¤ness, damping forces and earthquake. Fuzzy logic model is used to identify and compensate the uncertainty associated with the modeling equation. We prove that the closed-loop system is uniformly stable using Lyapunov stability analysis. The experimental result reveals that discrete-time sliding mode controller offers significant vibration attenuation with active mass damper and torsional actuator.